Adsorbed states and the kinetics of electrooxidation of phenols on metal oxides - Borras, Carlos; Mostany, Jorge; Scharifker, Benjamín (Ciencia, 1970)
We discuss the role of adsorbed states in determining the kinetics of electrochemical oxidation of substituted phenols on various metal oxide surfaces. On antimony-doped tin oxide (SnO2,-Sb) electrodes, oxidation of both p-methoxyphenol (PMP) and p-nitrophenol (PNP) follow Langmuir-Hinshelwood kinetics; at high concentrations of phenol in solution, the oxidation rates are controlled by surface processes. In general, anodic oxidation of PMP and PNP on SnO2-Sb electrodes leads to complete mineralization to CO2. Under surface saturation conditions, however, oxidation of PNP occurs to a lower extent due to the encumbered formation of OH surface species required for complete oxidation. The role of adsorbed states is further illustrated examining the effects of competing adsorption of p-chlorophenol (PCP) and PNP on bismuth- doped lead oxide (PbO2-Bi) electrodes. It is shown that due to stronger adsorption, the presence of PNP inhibits the oxidation of PCP.